Normandy 1944 : Allied landings and breakout - Badsey, Stephen (London : Osprey, 1990)
"D-Day, 6 June 1944, saw the largest amphibious landing operation in history. From ports and harbors and the southern coast of England, an armada of troopships and landing craft launched the Allied assault on the mainland of Europe. Stephen Badsey provides a concise account of the Normandy campaign, from the fiercely contested landings, to the struggle to capture Caen, the 'Cobra' breakout and the dramatic pursuit of the Germans to the River Seine. This was the crucial campaign of the Western theater, after the Battle of Normandy the only question was how soon the war would end, not who would win it."--BOOK JACKET.
The origins of the Battle -- The opposing commanders: The German commanders ; The Allied commanders -- The opposing Armies: The German forces ; The Allied forces -- The opposing plans: The German plans ; The Allied plans -- The Battle of Normandy: The Allied landings, 6 to 7 June ; Securing the beachhead, 7 to 17 June ; The break-in, 18 to 24 June ; the breakthrough, 25 June to 10 July ; The breakout, 10 July to 5 August ; the exploitation, 5 to 11 August ; The encirclement, 11 to 25 August -- The aftermath of the battle -- Chronology -- The battlefield today -- Wargaming Normandy: High Command ; Tactical games ; In conclusion.
Includes bibliographical references (page 92).
Keywords: 1939-1945; World War, 1939-1945 -- Campaigns -- France -- Normandy; Military campaigns; France -- Normandy; World War 2 -- Normandy campaign